Moderate deviations and central limit theorem for positive diffusions - Yumeng Li; Shuguang Zhang (Journal of Inequalities and Applications, 2016)
Abstract In this paper, we establish a central limit theorem and a moderate deviation principle for the positive diffusions, including the CEV and CIR models. The proof is based on the exponential approximations theorem and Burkholder-Davis-Gundy’s inequality.